Odpowiedzi

2010-03-08T18:16:56+01:00
A) -3x = 2x - 10
-3x-2x=-10
-5x=-10/÷(-5)
x=2

b) 2x - 2 = 7 - x
2x+x=7+2
3x=9/÷3
x=3
c) 10 = 4 - 2x
6=-2x/÷(-2)
x=-3

d) -(2x - 1) = 4
-2x+1=4
-2x=3/÷(-2)
x=-3/2=-1 i 1/2
Najlepsza Odpowiedź!
2010-03-08T18:18:37+01:00
A
10=2x+3x
10=5x /5
x=2

b
2x+x=7+2
3x=9 /3
x=3

c
2x=4-10
2x=-6 /2
x=-3

d
-2x+1=4
-2x=4-1
-2x=3 /-2
x=-1,5
2010-03-08T18:19:53+01:00
A) -3x = 2x - 10 / -2x
-5x = -10 / : (-5)
x = 2

b) 2x - 2 = 7 - x / +x
3x - 2 = 7 / +2
3x = 9 / :3
x =3

c) 10 = 4 - 2x / -4
6 = -2x / :(-2)
x = -3

d) -(2x - 1) = 4
-2x + 1 = 4 / -1
-2x = 3 / :(-2)
x = -1,5
3 1 3